Ladybug Girl and the Big Snow - Soman, David; Davis, Jacky 1966- (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) Inc., 2013)
Wearing her ladybug costume, Lulu plays in new fallen snow.
Keywords: Snow -- Juvenile fiction; Imagination -- Juvenile fiction; Snow -- Fiction; Imagination -- Fiction